Sikap dan Strategi Orang Tua terhadap Pengembangan Kemampuan Multibahasa Anak di Daerah Kuta Bali - Putra, I Gde Agoes Caskara Surya; Gorda, A.A.A Ngurah Tini Rusmini (Jurnal Kajian Bali (Journal of Bali Studies); Vol 11 No 2 (2021): Volume 11 No. 2. Oktober 2021DO - 10.24843/JKB.2021.v11.i02.p12, 2021)
This study aims to find out Kutanese parents’ attitudes towards Balinese, Indonesian, and Englis, as well as their strategies to develop their children language abilities. Participants in this study were twelve parents. The method for collecting the data was recorded interview and the recordings were then transcribed to facilitate research. The data was analized using family language policy and language strategies theories. Based on the research results, it can be concluded that the participants have very positive attitudes towards Balinese, Indonesian and English. Their positive attitude is also in line with the strategy they are doing, where they want their children to grow up as multilingual children. Of the three languages, English is the language with the most varied strategies.